Motivation, Gender, and Possible Selves. Issue 2 (5th April 2013) - Henry, Alastair; Cliffordson, Christina
Abstract : Despite the consistency with which gender differences have been found in second language motivation, little systematic research has taken place on motivation and gender to date. Permeating self‐concept development, gender impacts not only current selves but also future‐oriented possible selves. In construing possible selves, females tend to emphasize interdependence, meaning they invest more in interpersonal relationships and self–other interaction. Based on instruments measuring ideal language‐speaking/using selves and an interdependent self‐construal in a sample of 140 female and 129 male adolescents enrolled in the final year of secondary education in Sweden, and using confirmatory factor analysis, support was found for the hypothesis that gender‐related variance on a measure of the ideal language‐speaking/using self could be accounted for by an interdependent self‐construal. In discussing the results, further avenues for exploring the impact of gender on possible selves using more contextually sensitive research designs are presented.